2020
DOI: 10.1002/adfm.202004119
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Modularity of Biomaterial Carriers to Tune Immune Responses

Abstract: Biomaterial carriers offer modular features to control the delivery and presentation of vaccines and immunotherapies. This tunability is a distinct capability of biomaterials. Understanding how tunable material features impact immune responses is important to improve vaccine and immunotherapy design, as well as clinical translation. Here the modularity of biomaterial properties is discussed as a means of controlling encounters with immune signals across scales-tissue, cell, molecular, and time-and ultimately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 149 publications
(242 reference statements)
0
13
0
Order By: Relevance
“…An appropriate biodegradable porous scaffold can mimic the ECM for cell attachment, proliferation and differentiation of cells in bone tissue engineering [ 245 ]. Accumulated studies have revealed that the implanted biomaterials can play an important role in the regulation of biological activity of host cells [ 246–248 ]. Scientists thereby began to seek an approach that enables biomaterials to stimulate host cells to function in angiogenesis.…”
Section: Applications Of Biomaterials In Tissue Regenerationmentioning
confidence: 99%
“…An appropriate biodegradable porous scaffold can mimic the ECM for cell attachment, proliferation and differentiation of cells in bone tissue engineering [ 245 ]. Accumulated studies have revealed that the implanted biomaterials can play an important role in the regulation of biological activity of host cells [ 246–248 ]. Scientists thereby began to seek an approach that enables biomaterials to stimulate host cells to function in angiogenesis.…”
Section: Applications Of Biomaterials In Tissue Regenerationmentioning
confidence: 99%
“…17, 38-40 A growing body of work demonstrated that immune cells require precise spatial and temporal cues to drive specified responses, supporting the idea that spatiotemporal control of vaccines can have a profound effect on the magnitude and quality of the immune response. 41-50…”
Section: Introductionmentioning
confidence: 99%
“…17,[38][39][40] A growing body of work demonstrated that immune cells require precise spatial and temporal cues to drive specified responses, supporting the idea that spatiotemporal control of vaccines can have a profound effect on the magnitude and quality of the immune response. [41][42][43][44][45][46][47][48][49][50] The precise spatiotemporal control of vaccines can also be achieved by localized slow delivery of vaccine components. Recent proof-of-concept studies have shown that sustained release of an HIV vaccine through implantable osmotic pumps led to greatly improved quality of vaccine responses, such as durable germinal center (GC) responses, high antibody titers, and development of better virus neutralization compared to standard soluble administration of the same vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Across these categories, a generally attractive feature is the ability for improved levels of control. For example, many biomaterials provide tunable control over loading and release of multiple immune cues, targeting specific cells or tissues, cargo protection, and control over release kinetics (13). The ability to chemically modify and functionalize the surface of nano-or microparticles also offers a modular ability that is particularly attractive in displaying immune cues to direct immune processes (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%